IMPLEMENTASI POJOK BACA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA (STUDI EKSPLORASI GERAKAN LITERASI SEKOLAH) - Coo, Reldiana Lidivika; Qondias, Dimas; Kaka, Pelipus Wungo; Wau, Maria Patrisia (Dharmas Education Journal (DE_Journal), 2024)
This research examines the implementation of the Reading Corner program as part of the School Literacy Movement to improve students' reading abilities. Reading literacy activity index data on a national scale, East Nusa Tenggara (NTT) Province occupies 31st position out of 34 provinces in Indonesia. These results are answered by the phenomenon in the field, there are still elementary school students who are not yet fluent in reading. The aim of this research is to determine the implementation of reading corners to improve elementary school students' reading literacy. Qualitative research uses observation, interviews, documentation. Data were analyzed descriptively. The research results show that the Reading Corner plays a positive role in increasing students' access to reading materials and creating an environment that supports literacy culture. However, several obstacles were also found, such as limited book collections and a lack of active participation from all school members. This research provides recommendations for developing a more effective Reading Corner program in supporting the improvement of students' reading abilities. The results of the study on the implementation of the reading corner showed that 73% of students read fluently, 27% had difficulty. The implementation of the reading corner is successful but needs optimization.